2014
DOI: 10.1007/s10620-013-3017-y
|View full text |Cite
|
Sign up to set email alerts
|

Once-Daily Omeprazole/Sodium Bicarbonate Heals Severe Refractory Reflux Esophagitis with Morning or Nighttime Dosing

Abstract: Once-daily IR-OME (taken morning or night) effectively heals severe reflux esophagitis and improves GERD symptoms. Results support the clinical practice recommendation to repeat EGD after 8 weeks PPI therapy in severe esophagitis patients to assure healing and exclude Barrett's esophagus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The IR‐OME formulation evaluated in the present study is known to heal severe reflux esophagitis, improve GERD symptoms such as heartburn (Orbelo et al. ), and has shown promise in mitigating a delayed onset of action (Howden ). The incorporation of sodium bicarbonate in the formulation of IR‐OME provides rapid buffering of gastric acidity thereby protecting the IR drug from inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…The IR‐OME formulation evaluated in the present study is known to heal severe reflux esophagitis, improve GERD symptoms such as heartburn (Orbelo et al. ), and has shown promise in mitigating a delayed onset of action (Howden ). The incorporation of sodium bicarbonate in the formulation of IR‐OME provides rapid buffering of gastric acidity thereby protecting the IR drug from inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study revealed that SR baclofen plus omeprazole is more effective than omeprazole alone in the treatment of reflux symptoms (heartburn and regurgitation) ( 31 ). Another study which was conducted to compare the effects of single-dose morning versus nighttime once-daily omeprazole/sodium bicarbonate (Zegerid (®) (IR-OME) in patients with esophagitis and symptoms of gastroesophageal reflux, showed that the reflux esophagitis and GERD symptoms improved after taking IR-OME ( 32 33 ). According to the study of Kim et al, poor response to PPI treatment is a result of psychological factors, sleep dysfunction and BMI lower 23kg/m in patients with GERD symptoms ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…14 Once daily morning or bed time omeprazole/sodium bicarbonate was found effective in improving severe reflux esophagitis and GERD symptoms. 15 In another study by Barrett's oesophagus along with complete control of oesophageal pH during 97% of the 24-h recording periods. 16 Omeprazole-sodium bicarbonate was not found more effective than omeprazole in treatment of GERD however, it showed the more sustained relief and effect in systematic review by Higuera-de-la-Tijera.…”
Section: Discussionmentioning
confidence: 99%